INTERVENSI KEMENTERIAN DESA PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI DALAM IMPLEMENTASI KEBIJAKAN PERCEPATAN PENURUNAN STUNTING DI DESA - Fajri Maulana; Mala Sondang Silitonga; Asropi (Journal Publicuho, 2023)
Stunting is a crucial problem in Indonesia and requires collaborative action by multiple stakeholders. The policy to accelerate stunting reduction was designed with a convergence strategy involving ministries and government officials at the village level. The purpose of this study is to analyze the intervention of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration in implementing stunting reduction policies in villages. The research paradigm used is post-positivist with qualitative methods. The data collection process was carried out by interviews and analysis of policy documents. The results of this research show that the intervention carried out by the village ministry took the form of a facilitation program and regulatory support. The interventions carried out are still on track and quite effective in achieving policy targets. Recommendations from the research include strengthening communication between central agencies to village parties with intensive coordination, expanding funding networks, and carrying out collaborative actions to increase the impact of policies.